The Level of Mental Health among Omani Students with Learning Disabilities during Coronavirus Pandemic from their Parents’ Perspective - Al-Hinai, Maryam Hafiz; Al-Zoubi, Suhail Mahmoud; Shebani, Zubaida Sulaiman (Journal of Educational and Psychological Sciences, 2024)
This study aimed to identify the level of mental health among Omani students with learning disabilities (SLDs) during the Coronavirus pandemic from their parents’ perspective. The study sample consisted of 288 male and female. They were enrolled in the resource room program in the First-Cycle Schools in Muscat Governorate, Oman. The parents of Omani SLDs responded to the mental health scale. This scale consisted of 27 items distributed to four domains related to sleep disorders, depression, fear, and anxiety. The results indicated that the level of mental health among Omani SLDs was average on all domains of the scale. The results also showed that there were statistically significant differences according to the gender in favor of females. Moreover, the results showed that there were no statistically significant differences due to the category of learning disabilities. The study recommended designing counseling programs to reduce the impacts of the Coronavirus on SLDs and conducting a literature review to identify the impacts of the pandemic on SLDs in Arab society.